Koi baat nahi - Attiya Naqvi (2002)
Koi Baat Nahin," which translates to "No Problem" or "It's Okay," is a poetic exploration by Atiya Naqvi that captures a wide range of emotions and experiences through elegant Urdu verses. The collection is celebrated for its emotional depth and lyrical beauty